1996
DOI: 10.1177/030098589603300203
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Immunohistochemical Characterization of Hemangiomas in the Skin of Seven Young Horses

Abstract: Abstract. The histologic and immunochemical characteristics of benign vascular tumors excised from the skin of seven young horses were evaluated. The patients were male horses of various breeds and were 16 months of age or younger at the time of presentation. Six tumors occurred on the extremities, and one was removed from the lip. Histologically, most tumors consisted of cellular nodules of varying compactness with few to many blood-filled lumina. Nodular growth separated preexisting adnexa and subcutaneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
59
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 15 publications
5
59
0
7
Order By: Relevance
“…This neoplasm has been reported mainly in the skin of limbs, with a multifocal growing pattern [7], which is in agreement with the two reported cases. Some authors reported the invasion of adjacent structures such as tendon and synovial sheath [3,8].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This neoplasm has been reported mainly in the skin of limbs, with a multifocal growing pattern [7], which is in agreement with the two reported cases. Some authors reported the invasion of adjacent structures such as tendon and synovial sheath [3,8].…”
Section: Resultssupporting
confidence: 92%
“…The wall of larger proliferated vessels also presented muscle actin-and desmin-positive spindle cells resembling pericytes/smooth muscle cells. This pattern was reported in 7 of 9 cutaneous hemangiomas in young horses [7].…”
Section: Resultssupporting
confidence: 59%
“…This form may occur in an enzootic form (5 (18,42) or not recognized (56). It is conceivable however, that papillomavirus might occasionally exist in a latent form in utero and becomes manifest when fetal skin attains a critical level of maturation (56 (23,28,29,69). The fact that most cases occurred in horses that were less than one year old and that at least 11 foals (table 2) An interesting lesion was reported to occur in a newborn filly (54).…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…8,11,13 Positive staining for factor VIII-related antigen was strongest in nonneoplastic endothelial cells of small capillaries, arterioles, and veins (Fig. 5).…”
Section: Intrapelvic Hemangiosarcoma In a Horsementioning
confidence: 95%